PROAHS: protocolo de identificação de discentes com indicadores de altas habilidades/superdotação no ensino superior - REIS, Grasiano Vieira (Universidade Federal do Pará, 2024)
The research aimed to develop a protocol to contribute to the identification of students with indicators of high abilities/giftedness in higher education. This proposal arose from the need for protocols to identify students with indicators of high skills/giftedness in higher education, which can contribute to the creation of records for this special education audience by universities, based on the Accessibility Centers, as already pointed out in National Education Guidelines and Bases Law (LDBEN) – Law No. 9,394, of 1996 (Brazil, 1996). The epistemological bases for the research were the theories that support protocols for identifying high abilities/giftedness. The main theory of the research and educational product is Renzulli's Three Ring Model (1986). The methodology is exploratory with a qualitative nature. The educational product is a protocol, called “PROAHS: Protocol for identifying students with indicators of High Skills/Giftedness in Higher Education”, created in the format of a Portable Document Format (PDF) for presentation and availability. The platform used to create the product was Canva. The Design thinking approach was used as part of the methodological process for creating the product. The steps and content of the protocol are based on Renzulli's Three Ring Model (1986). The forms used were created and adapted from models aimed at Basic Education, since it was identified that there were no protocols for the public studied in this research in Higher Education. The protocol is organized as follows: the initial part provides a contextualization of Accessibility Cores, high abilities/giftedness and Renzulli's Three Rings Theory. After the topics, there are the five steps listed for the student identification process. The validation of the product was carried out with 06 coordinators from the Accessibility Center in the North Region and 01 coordinator from the High Skills/Giftedness Activity Center in Pará. The result pointed to the Accessibility Centers as one of the possible spaces to use the product, which it was also considered as a viable alternative for the initial identification of students in higher education institutions. Thus, the protocol is another tool to help education professionals, which aims to guarantee the right to educational assistance for students with high skills/giftedness in Higher Education, Special Education audiences.